Students' Numeracy Skills Relating to Algebra Topic Using COVID-19 Context - Sari, Septi Puspita; Zulkardi, Zulkardi; Darmawijoyo, Darmawijoyo (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The Minimum Competency Assessment (MCA) is a basic competency assessment that will be carried out by the ministry of education and culture in Indonesia in 2021, one of the assessments is numeracy. Algebraic material is one of the important materials for students to learn related to everyday problems. The use of context is important in learning algebra. In this regard, the discussion which is now a topic of discussion for all groups not only from Indonesia but the world, namely Covid-19, can be an interesting context to raise. This study, describes the numeracy skills of students in working on algebraic questions, research subjects are students with heterogeneous abilities (medium, high, low) using a descriptive qualitative approach, with collection techniques in the form of tests, and interviews. The research subjects were grade VII students. Wherefrom the research, it was found that there were still unfulfilled numerical indicators, namely indicators of interpreting it to conclude. While indicators that often appear are using numbers and mathematical symbols in solving problems in life.